The Implementation of STEM in Science Learning to Enhance Creativity and Critical Thinking Skills of Students at SDN 2 Jayapura - Golden Ringgo SC. Ayomi; Lina Febriani Tehuajo; Mamberuman Marthen Inggamer (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to explore the implementation of the STEM (Science, Technology, Engineering, and Mathematics) approach in science education at SDN 2 Jayapura and its impact on enhancing students' creativity and critical thinking skills. A quasi-experimental method with a pre-test and post-test design was used. Students were divided into two groups: the experimental group, which received STEM-based instruction, and the control group, which received conventional instruction. Data were collected through creativity tests, critical thinking tests, and student participation observations. The results show that the experimental group experienced a significant increase in creativity and critical thinking skills after participating in the STEM-based instruction, while the control group showed more limited improvement. These findings support that STEM-based learning can enhance students' critical thinking and creativity, as well as link science concepts to practical applications in everyday life. This study provides an important contribution to the development of innovative and effective science education curricula and teaching methodologies, especially in areas with geographical challenges and limited resources.